2021
DOI: 10.21608/ejom.2021.143348
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Perceived Work Ability and Its Determinants among Healthcare Providers

Abstract: Introduction: Healthcare providers are at high risk of occupational stress, burnout, health hazards and job dissatisfaction which can have harmful consequences on their health, work ability and professional efficiency. Therefore, it is important to adopt strategies for the promotion of healthy working conditions and improvement of their work ability. Aim of work: To assess the perceived work ability and its dimensions among the healthcare providers at Minia city, Egypt and identifies its relationship with soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
2
4
2
Order By: Relevance
“…The aim of this study was to determine perceived work ability and its associated factors among nurses working in the Northwest of Amhara regional state Referral Hospitals, Northwest Ethiopia. The result of the current study showed that 242(59.0%) (CI = 53.7%, 64.3%) nurses had poor level of work ability, which is higher than the studies done in Egypt [ 14 ] and Nigeria [ 15 ]. In Nigeria, 29.2% of study participants had a poor level of work ability [ 15 ].…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…The aim of this study was to determine perceived work ability and its associated factors among nurses working in the Northwest of Amhara regional state Referral Hospitals, Northwest Ethiopia. The result of the current study showed that 242(59.0%) (CI = 53.7%, 64.3%) nurses had poor level of work ability, which is higher than the studies done in Egypt [ 14 ] and Nigeria [ 15 ]. In Nigeria, 29.2% of study participants had a poor level of work ability [ 15 ].…”
Section: Discussioncontrasting
confidence: 71%
“…In this study, the prevalence of poor level of work ability was higher than the study done in Egypt (14.1%) [ 14 ]. The possible explanation for these differences might be methodological differences, socioeconomic development differences, organizational and work-related factors.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations